FUZZY SETS AND FUZZY LOGIC WITH ENGINEERING APPLICATIONS - ROSS, TIMOTHY J. (New Delhi Wiley, 2021)
Considers potential applications and use cases, business opportunities that can arise, and how standardization activities are shaped. Covers the technical findings of the two-year EC H2020 5G PPP 5GCAR project, a comprehensive collaborative research initiative between telecommunications and automotive industries, as well as academic researchers
https://ebooks.wileyindia.com/product/fuzzy-sets-logic-engineering-applications-4ed-indian-adaptation
Keywords: Maths; Fuzzy sets; Fuzzy logic